Effect of Coriander Seeds as Diet Ingredient on Blood Parameters of Broiler Chicks Raised under High Ambient Temperature - Al-Jaff, Farah K. (International Journal of Poultry Science, 2011)
This Study was conducted to investigate the potential effect of coriander seeds on physiological traits. One hundred and eighty day-old Arbor Acer broiler chick were randomly assigned to four dietary treatments with three replicate pens (15 birds/pen). Birds were fed experimental diets containing 0% (T1), 1% (T2), 2% (T3) and 3% (T4) coriander seed. Feed and water were provided ad libitum during the experiment. Performance and physiological parameters were monitored at the end of the study (6 weeks of age) which includes live body weight, feed conversion ratio (g. Feed gain/g. Gain) total protein, albumin, globulin, A/G ratio, GTP, GOT, Alkaline phosphatase, glucose, cholesterol, LDL, HDL, Triglycerides, phospholipids, uric acid, creatinine and antibody titer (ND). Results showed that final body weight was (p